Primary Sjögren syndrome clinical and prognostic correlation - Mahgoub, Narden (faculty of Basic Medical Science - Libyan International Medical University, 2020)
Sjogren's syndrome (SS) is a slowly progressing autoimmune disease, affecting predominantly middle-aged women, with a female to male ratio reaching 9:1. It is characterized by lymphocytic infiltration of the exocrine glands, mainly the lacrimal and salivary glands, resulting in reduced secretory functions and oral and ocular dryness. The syndrome can present alone as primary SS ( pSS ) or in the context of underlying connective tissue disease as secondary SS (sSS).While the pathogenesis of the disease remains elusive, environmental, genetic and hormonal contributors seem to be involved. Over the last years, compelling evidence has suggested a pivotal role of the epithelium in orchestrating the immune response in the histopathological lesion of Sjogren's syndrome and the term “autoimmune epithelitis” has been proposed as an etiological term.
Sjögren's syndrome (SS) is a chronic autoimmune disorder characterized by decrease salivary and lacrimal gland function, due to lymphocytic infiltration of these glands, leading to progressive destruction, Sjogren‟s syndrome is a multifactorial condition with genetic, environmental and hormonal factors playing a role in establishing the condition. B-cell activating factor (BAFF) is an important mediator in the induction and perpetuation of this condition patients are classified as having primary SS (pSS) and secondary SS. In pSS, decreased exocrine gland function leads to the „sicca complex‟, a combination of dry eyes ( Xerophthalmia ) and dry mouth (xerostomia). Secondary SS (sSS) is associated with other rheumatic conditions, of which the most common is rheumatoid arthritis .